Effect of airbrush type on sprayed platinum and platinum-cobalt catalyst inks: Benchmarking as PEMFC and performance in an electrochemical hydrogen pump. (16th October 2020) - Arenas, Luis F.; Hadjigeorgiou, Georgios; Jones, Simon; Van Dijk, Nick; Hodgson, David; Cruden, Andy; Ponce de León, Carlos
Abstract: Proton-exchange membrane fuel cells and electrochemical hydrogen pumps are based on membrane electrode assemblies containing Pt catalysts. During their preparation, a catalyst ink is usually applied to the gas diffusion layer. Among the available methods, ink spray using an airbrush can be advantageous for making electrodes at universities and companies. This work compares the suitability of gravity-feed and suction-feed airbrushes during the evaluation of in-house developed Pt and Pt–Co catalysts. The surface morphology of the catalyst layers was analysed by SEM and EDS and related to the preparation technique. The catalysts were compared against an off-the-shelf commercial catalyst. The in-house Pt catalyst afforded similar polarisation curves as the commercial catalyst whereas the Pt–Co catalyst exhibited a slightly lower performance. The suction-feed airbrush was deemed preferable because it produced cracked mud-like, homogeneous and smoother catalyst layers in contrast to the gravity-feed method, which resulted in poor-quality deposits with loose particles, lower Pt utilisation and higher resistance. Graphical abstract: Image 1 Highlights: In-house developed Pt and Pt–Co catalysts are tested in reproducible MEAs. The effect of gravity- and suction-fed airbrushes on the catalyst layer is studied. Catalysts are benchmarked against Hi-Spec 3000 in fuel cell & H2 pump modes. Suction-fed airbrushes are better for providing a 'cracked mudflat' morphology. In-house Pt catalyst was alike Hi-Spec but the Pt–Co catalyst underperformed.